The impact of copper production from manganese nodules: A simulation study - Gerhard Wagenhals (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
The first part of the paper describes the main features of the world copper industry, including consumption, inventories, prices, trade, primary and secondary supply as well as reserves and resources. In the second part an econometric model of the world copper market is derived; theoretical and empirical justifications are provided for some representative equations. Finally, the third part of the paper deals with the results of forecasting and simulation experiments performed with this model. A conditional forecast of the major future developments in the world copper industry and an assessment of the likely impact of ocean floor mining on the copper market constitute the main topics discussed in this part. Base case simulation results (without seabed mining) are reported and compared to three alternative scenarios assuming different recovery rates for copper from deep sea manganese nodules.
Keywords: 330